A Randomized Phase II Study of S-1 Adjuvant Chemotherapy With or Without Hochu-ekki-to, a Japanese Herbal Medicine, for Stage II/III Gastric Cancer: The KUGC07 (SHOT) Trial - Okabe, Hiroshi; Kinjo, Yousuke; Obama, Kazutaka; Hosogi, Hisahiro; Hata, Hiroaki; Asao, Yoshito; Harada, Hideki; Manaka, Dai; Itami, Atsushi; Teramukai, Satoshi; Sakai, Yoshiharu (Frontiers in Oncology, 2019)
Objectives: A multicenter randomized phase II study was conducted to evaluate the effects of Hochu-ekki-to (TJ-41) for reducing adverse reactions and increasing compliance with S-1 adjuvant therapy for advanced gastric cancer. Methods: The eligibility criteria were pathological stage II/III after R0 resection. Patients received adjuvant therapy with S-1 alone (group S) or S-1 with TJ-41 (group ST) for one year. The primary endpoint was the completion rate of S-1. Secondary endpoints were adverse events, relative dose intensity, relapse-free survival (RFS), and overall survival (OS). Results: We randomly assigned 56 patients to group ST and 57 patients to group S. The completion rates of S-1 were 54.5% and 50.9%, the median relative dose intensities were 89.2% and 71.9%, and adverse events of grade 3 or 4 occurred in 45.5% and 54.5% in groups ST and S, respectively. There was no significant difference in 3-year OS or RFS between the two groups. Conclusions: A higher completion rate, higher relative dose, and less frequent toxicity of S-1 were found in group ST, but the differences were not significant. TJ-41 may reduce toxic effects and increase compliance with S-1, but our findings do not support routine use of TJ-41 after gastrectomy.